2024
DOI: 10.1039/d4ra00291a
|View full text |Cite|
|
Sign up to set email alerts
|

Innovative snail-mucus-extract (SME)-coated nanoparticles exhibit anti-inflammatory and anti-proliferative effects for potential skin cancer prevention and treatment

Consoli Valeria,
Petralia Salvatore,
Vanella Luca
et al.

Abstract: Nowadays, several studies have highlighted the ability of snail mucus in maintaining healthy skin conditions due to its emollient, regenerative and protective properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Many reports of antibacterial, antifungal, larvicidal, anti-termite [ 61 , 62 , 63 , 64 , 65 ], and anticancer [ 66 , 67 ] activities of CuONPs derived from plants, animals, and microorganisms. Furthermore, several studies conducted in recent years have demonstrated the advantages of employing snail mucus to synthesize Ag and AuNPs, which have been shown to have broad-spectrum antibacterial activity, anticancer potential, and anti-inflammatory properties [ 21 , 68 ]. Based on the presented investigations, it can be assumed that CuONPs obtained from the C. aspersum mucus with MW > 20 kDa also show in vitro antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports of antibacterial, antifungal, larvicidal, anti-termite [ 61 , 62 , 63 , 64 , 65 ], and anticancer [ 66 , 67 ] activities of CuONPs derived from plants, animals, and microorganisms. Furthermore, several studies conducted in recent years have demonstrated the advantages of employing snail mucus to synthesize Ag and AuNPs, which have been shown to have broad-spectrum antibacterial activity, anticancer potential, and anti-inflammatory properties [ 21 , 68 ]. Based on the presented investigations, it can be assumed that CuONPs obtained from the C. aspersum mucus with MW > 20 kDa also show in vitro antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%